Song and Self-Discovery: Touching the Pattern that Connects - Wersal, Lisa (Voices: A World Forum for Music Therapy, 2006)
This essay is a personal account of the power of song in health recovery and self-discovery. It follows the author’s process of grappling with questions of where beauty lies and how to access it, and of the interplay and co-creation between artist, art, and perceiver. The author highlights music’s "resolving" qualities: helping one to resolve past issues and hurt, and to strengthen one’s resolve to heal. Told in an appreciative tone, this is a story of synergy and healing. Together, we sing our world into being.